Implementation of English Language Acquisition with the Phonics Method (Multi-site Study at Hasanuddin Madjedi and Madinaturramlah Islamic Integrated Early Childhood Center in Banjarmasin City) - Redhamah, Gadis; Jamain, Ririanti Rachmayani; Noorhapizah, Noorhapizah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the implementation of English language acquisition with the phonics method in learning and describe in depth and analyze in detail the competence of teachers in the effort to implement English language acquisition with the phonics method . The researcher acted as a participant who observed the location, environmental conditions, relevant resources and stages of strategic management at Hasanuddin Madjedi Islamic Integrated Preschool and Madinaturramlah Islamic Integrated Preschool. Data analysis using Miles, Huberman & Saldana is with the following stages: data condensation, data display, and conclusion drawing and verification. The results showed that the acquisition of English with the phonics method, among others, with song movements, introduction of self-identity, contextual object names, letter separation (spelling) and letter sounds.